The Relationship Between Work-life Balance and Performance of Teachers in Malacca - Wan, Wu Ying; Shahrul Nizam Salahudin (Research in Management of Technology and Business, 2023)
This study intends to identify the relationship between work-life balance and performance of teachers in Malacca. Work-life balance refers to the working arrangements that ensure an employee’s personal and professional duties are balanced. Lack of the work-life balance will influence the performance of teachers. This is due to the numerous tasks that they must complete such as education and teaching, research and development and public service. The objectives of this study is to identify the level of work-life balance of teachers in Malacca, to identify the level of performance of teachers in Malacca and to identify the relationship between work-life balance and performance of teacher in Malacca. This study adopted quantitative research method, collecting the data from teachers who teach in primary school in Malacca. There are 266 teachers had been answer the questionnaire. Data collected were analyzed using Statistical Package for Social Science (SPSS). The findings demonstrated a correlation between work-life balance and performance of teachers in Malacca. Work-life balance and performance of teachers in Malacca have the significant positive correlation. However, the study suggests that in order to improve effective performance of teachers, work-life balance must be increased.